Microcontroller Based Automatic Calculation of Ideal Weight Body - Mustar, Muhamad Yusvin; Chamim, Anna Nur Nazilah; Putra, Karisma Trinanda; Nugraha, Vendy Dwi Hendra; Jusman, Yessi (Journal of Electrical Technology UMY, 2018)
The development of science and technology is increasing every day, especially in the field of electronics and control systems. This is marked by the rapid progress that has occurred with the creation of increasingly sophisticated electronic devices and all systems have gone from conventional to automatic. Many benefits are obtained from the rapid development in the field of electronics and control systems including being able to assist humans in completing their tasks, increasing human productivity, and increasing the level of effectiveness in doing work. Departing from this, then in this study designed an automatic body ideal value calculation tool that is controlled by a microcontroller chip using C language programming. This study provides another alternative in measuring mass values, height values, and displaying a BMI (Body Mass Index) ) subject automatically. The working system is quite easy where the subject only climbs the scales, the height measuring device with ultrasonic sensors PING)) will work to measure the subject's height, the scales equipped with the HX711 module will measure the mass value of the subject. Then, the microcontroller will process the height value, and the mass value of the subject to calculate the subject's BMI